Profile of nutritional status of children and adolescents from Bogotá, Colombia. The FUPRECOL study (2016)
Introduction: This study aimed to analyze the nutritional status among Colombian children and adolescents and to determine the relationship between the nutritional status according to the body mass index (BMI) and the waist circumference (WC). Methods: A cross-sectional study was conducted in 6.383 children and adolescents with age of 9 to 17.9 years old from Bogota, Colombia. Participants completed the Krece Plus questionnaire validated by the enKid study as an indicator of the nutritional level with the following categories: high (test ? 9), medium (test 6-8) and low (test ? 5). Other measures were: weight, height, WC and BMI as markers of the nutritional status. Results: Overall, 57.9% of the participants were girls (mean age 12.7 ± 2.3 years old). The nutritional status was low without large differences by sex and decreasing by age. In all categories of BMI, over 50% of boys and girls follow lower-quality diet, shown worse with advancing age. In both sexes, trends were observed between low nutritional level with the development of overweight. Also, WC was associated with a lower score in the Krece Plus in both sexes. Conclusions: The low nutritional level is related to changes in the nutritional status (WC and BMI) in scholars from Bogota. These findings may encourage further interventions for the improvement of nutritional habits among scholars from Colombia. © 2016, Grupo Aula Medica S.A. All rights reserved.